1989
DOI: 10.1207/s15328023top1604_1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Academic, Personal, and Career Development of Alumni from Southeast Missouri State University

Abstract: A survey containing institutional and program-specific items examined psychology and other graduates' evaluations of their undergraduate education (1 983-1 985) at Southeast Missouri State University. Psychology respondents resembled respondents from other majors in their social and personal interests, but differed from other resbondents in their educational and career attitudes. ~s~chology respondents were more likely to be enrolled in graduate coursework than were other respondents and indicated greater agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…Less is known about involvement in psychology extracurricular activities and satisfaction within the major. Early work showed that some major-specific experiences (e.g., fieldwork, faculty-guided research) were associated with psychology major satisfaction (Finney, Snell, & Sebby, 1989;Lunneborg, 1974). Additionally, students perceive psychology student organizations (e.g., Psychology Club, Psi Chi) to be rewarding and beneficial for graduate studies and a career in psychology (E. S. Nelson & Johnson, 1997;J.…”
mentioning
confidence: 99%
“…Less is known about involvement in psychology extracurricular activities and satisfaction within the major. Early work showed that some major-specific experiences (e.g., fieldwork, faculty-guided research) were associated with psychology major satisfaction (Finney, Snell, & Sebby, 1989;Lunneborg, 1974). Additionally, students perceive psychology student organizations (e.g., Psychology Club, Psi Chi) to be rewarding and beneficial for graduate studies and a career in psychology (E. S. Nelson & Johnson, 1997;J.…”
mentioning
confidence: 99%
“…In a survey of University of Washington baccalaureates, Lunneborg ( 1985) examined the current jobs held by 178 psychology graduates. Finney et al (1989) reported similar results: "48% of psychology respondents who were employed and 68% of the other respondents indicated that their jobs were in the field of their academic major" (p. 174). Thus, nearly 50% of the alumni worked in occupations not directly related to their psychology major, most of which were business related.…”
Section: Review Of Alumni Survey Literaturementioning
confidence: 75%
“…The psychology curriculum described by Finney et al (1989) illustrates this point. A final note on strategies for improving career relevance focuses on program structure, which can have a powerful influence on the choices students make.…”
Section: Strategiesmentioning
confidence: 93%
See 2 more Smart Citations